Análise ergonômica do trabalho de colheita de citros: comparativo dos métodos de colheita manual e semimecanizado - Costa, Simone Emmanuelle Alves (Universidade Federal de São Carlos, 2013)
The Brazilian citrus business occupies a prominent place in the international market, with great economic and social significance in foreign exchange earnings and employment in the country respectively. In recent decades, the industry has been changing due to cyclical economic reasons, and these changes affect the harvesting process. In this context, the mechanization of the mentioned process diffuses as a possible alternative to reduce costs and increase productivity. However, the adoption of these new technologies in Brazilian orchards lacks analysis from the perspective of health and productivity, as opposed to the consolidated manual harvesting. The aim of this study is to bring a qualitative and quantitative comparison of the impacts on working conditions and productivity, between the use of manual harvesting methods and of multi-platform in São Paulo State orchards. On this purpose, it was used the approach of ergonomics analysis, focusing on activity, evaluating times and repeatability of cycles, as well as the amount of movements performed and energy expenditure for each of the methods. The results indicated a pronounced physical stress on the use of manual harvesting with increased caloric expenditure and amount of movements required to complete the harvest cycle. Despite evidence of work intensification in the use of platforms, this method has increased its viability by reducing the main constraints identified in the analysis of the collector‟s activity, especially those related to the use of stairs, as well as maintaining the quality of the fruit harvested.
Keywords: Laranja - colheita; Biomecânica; Mecanização agrícola; Condições de trabalho; Ergonomia situada; Colheita de citros; Biomecânica; Ergonomics; Citrus harvesting; Mechanization; Biomechanics; Working conditions; ENGENHARIAS::ENGENHARIA DE PRODUCAO